2012
DOI: 10.12659/msm.882890
|View full text |Cite
|
Sign up to set email alerts
|

New quantitative patterns of the growing trachea in human fetuses

Abstract: SummaryBackgroundRapid progress in perinatal medicine has resulted in numerous tracheo-bronchial interventions on fetal and neonatal airways. The present study was performed to compile normative data for tracheal dimensions at varying gestational ages.Material/MethodsUsing anatomical dissection, digital image analysis (NIS-Elements BR 3.0) and statistical analysis (Wilcoxon signed-rank test, Student’s t test, one-way ANOVA, post-hoc Bonferroni test, linear and nonlinear regression analysis) a range of the 4 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 32 publications
2
31
1
Order By: Relevance
“…The present study constitutes the continuation of our previous morphometric studies on the normal evolution of the ascending aorta [22], aortic arch [23], and thoracic aorta [24], which provided both detailed normative ranges and growth patterns for these aortic segments during gestation. Because the existing data on the abdominal aorta have been precisely focused on its length and diameters only [18], the present study provides reference values and growth patterns for length, external diameters and volume of the abdominal aorta in human fetuses.…”
Section: Discussionmentioning
confidence: 90%
“…The present study constitutes the continuation of our previous morphometric studies on the normal evolution of the ascending aorta [22], aortic arch [23], and thoracic aorta [24], which provided both detailed normative ranges and growth patterns for these aortic segments during gestation. Because the existing data on the abdominal aorta have been precisely focused on its length and diameters only [18], the present study provides reference values and growth patterns for length, external diameters and volume of the abdominal aorta in human fetuses.…”
Section: Discussionmentioning
confidence: 90%
“…Twenty‐five studies were identified that represent airway dimensions in fetuses or premature infants, between 1923 and 2013 . The measured structures range from the thyroid to the two main bronchi and are summarized in Supplementary Appendix SI‐SIV under references superscripted as following numbers: 99 (MRI studies table), (anatomical studies table), 42 (X‐ray studies table), 101, 103, 106 (USG studies table). The scientific work by means of ultrasound only includes measurements of the diameter of the airways .…”
Section: Resultsmentioning
confidence: 99%
“…The first measurements go back almost 100 years, whilst the measuring scientific instruments have evolved steadily in recent years. In some scientific works, the measurement is performed directly on the freshpreparations, while in other studies, frozen, or epoxy resin or formalin fixations were embedded. Eight studies do not discuss fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations